Hormone-induced spawning of wild and captive-grown spotted rose snapper Lutjanus guttatus using carp pituitary suspension and human chorionic gonadotropin - Boza-Abarca, J (2011)
Hormone-induced spawning of the spotted rose snapper Lutjanus guttatus was studied using wild and cage-grown fish. Carp pituitary suspension (CPS) and human chorionic gonadotropin (hCG) were assessed. Wild females (0.7–2.1 kg body weight (BW), n = 18) were collected by hook and line in the Gulf of Nicoya, Costa Rica, to induce final maturation and ovulation in the laboratory. In the first experiment, five doses of CPS were evaluated and spawning was only observed at the higher doses (4.0 and 4.5 mg CPS kg–1 BW); the doses used were lower than for other species under similar conditions. In the second experiment, CPS and hCG protocols were compared using cage-grown broodstock (n = 30 females, 462–995 g; n = 60 males, 400–600 g); egg production was more consistent for the hCG protocol. In the third experiment, cage-grown fish (n = 12 females, 368–977 g; n = 24 males, 400–600 g) were used to assess the female response to hCG and the fertility of the spawned eggs; two successive injections of different hCG doses were tested. The results confirm that two successive doses of 900 and 700 IU hCG kg–1 BW result in the highest number of eggs spawned and the best fertilization rates